Morphological and molecular characteristics of adult worms of Gnathostoma Owen, 1836 (Nematoda) collected from domestic pigs in Dien Bien Province, northern Vietnam - Van Tuyen, Nguyen; Thi Kim Lan, Nguyen; Doanh, Pham Ngoc (Folia parasitologica, 2019)
Gnathostomes are of interest because of their unique appearance and medical importance. Among 13 valid species of the genus Gnathostoma Owen, 1836 (Nematoda: Spirurida), two species, G. doloresi Tubangui, 1925 and G. hispidum Fedtschenko, 1872, are parasites of pigs but their larvae can infect humans to cause gnathostomiasis. In this study, we collected adults of Gnathostoma sp. from the stomach of domestic pigs (Sus scrofa domesticus Linnaeus) from Dien Bien Province, northern Vietnam. Morphologically, nematodes found here are most similar to G. doloresi with a slight difference in the spicules of males. In contrast, they are genetically distinct from G. doloresi and other species of Gnathostoma in both ITS2 and cox1 sequences. The findings of the present study suggest that specimens of Gnathostoma sp. found in Dien Bien are likely a new species and emphasise the need of further studies on the taxonomy and phylogenetic relationship of species of Gnathostoma. Special attention should also be paid to swine and human gnathostomiasis in Dien Bien Province, Vietnam and the neighbouring areas of China and Laos.
Keywords: Animals; Female; Helminth Proteins; Electron Transport Complex IV; ženské pohlaví; Sus scrofa; gnathostomóza; Gnathostoma; South-East Asia.; cox1; respirační komplex IV; prasata; Swine Diseases; Vietnam; mezerníky ribozomální DNA; Phylogeny; Male; nemoci prasat; Swine; morphology; ITS2; Gnathostomatidae; DNA, Ribosomal Spacer; proteiny červů; zvířata; mužské pohlaví; fylogeneze; Gnathostomiasis